2007
DOI: 10.1103/physrevb.76.125321
|View full text |Cite
|
Sign up to set email alerts
|

Carrier multiplication in semiconductor nanocrystals via intraband optical transitions involving virtual biexciton states

Abstract: We propose and analyze a physical mechanism for photogeneration of multiexcitons by single photons ͑carrier multiplication͒ in semiconductor nanocrystals, which involves intraband optical transitions within the manifold of biexciton states. In this mechanism, a virtual biexciton is generated from nanocrystal vacuum by the Coulomb interaction between two valence-band electrons, which results in their transfer to the conduction band. The virtual biexciton is then converted into a real, energy-conserving biexcito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 13 publications
0
71
0
Order By: Relevance
“…In addition, the results reported by Ellingson et al demonstrated that measuring the exciton population by probing the photoinduced absorption associated with intraband transitions yielded QYs equivalent to those measured using the interband bleach approach introduced by Schaller. The 3E g onset initially claimed by Schaller and Klimov was later revised slightly to ∼ 2.85E g [72]. MEG measurements by Murphy and Beard et al on ∼ 5.4 nm diameter PbTe NCs also showed MEG [15], with a threshold for strong MEG at ∼ 3E g QYs similar to those reported for PbSe and PbS [14].…”
Section: Lead Salts -Pbse Pbs Pbte and Pbse-pbs Core-shell Ncsmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, the results reported by Ellingson et al demonstrated that measuring the exciton population by probing the photoinduced absorption associated with intraband transitions yielded QYs equivalent to those measured using the interband bleach approach introduced by Schaller. The 3E g onset initially claimed by Schaller and Klimov was later revised slightly to ∼ 2.85E g [72]. MEG measurements by Murphy and Beard et al on ∼ 5.4 nm diameter PbTe NCs also showed MEG [15], with a threshold for strong MEG at ∼ 3E g QYs similar to those reported for PbSe and PbS [14].…”
Section: Lead Salts -Pbse Pbs Pbte and Pbse-pbs Core-shell Ncsmentioning
confidence: 72%
“…In general there are three theories that have been proposed to explain efficient MEG in semiconductor NCs; (1) a coherent superposition of single and multiple exciton states [14,55]; (2) excitation of a virtual multiexciton state that is strongly coupled to a real multiexciton state [72,76] and (3) incoherent impact ionization, analogous to bulk impact ionization with proper modification of the electronic states [77,78].…”
Section: Theoretical Descriptions Of Multiple Exciton Generationmentioning
confidence: 99%
“…Previous studies of photogeneration processes [5,14], implicitly assumed constructive interference within the second and the third pathways. The assumption led to significant overestimation of photogeneration QE.…”
mentioning
confidence: 99%
“…From theory point of view, multiexciton photogeneration [5,14], coherent multiexciton production [15,16], and incoherent impact ionization (II) [17][18][19], are currently under debate as primary mechanisms of CM. The ab initio calculations on small clusters ( 1 nm) demonstrated the role of strong Coulomb correlations in multiexciton photogeneration and emphasized the role of fast exciton-biexciton dephasing [20].…”
mentioning
confidence: 99%
“…is an accepted mechanism, it is not yet clear if the same process is responsible for MEG in quantum-confined materials. The increased efficiency of MEG in these structures has not yet been fully explained and different models have been proposed where the multi-excitonic state is created through an excited virtual multi-excitonic state [42,43] or via an instantly generated superposition of single-and multi-excitonic state [41,44].…”
Section: Enhancing CM In Qdsmentioning
confidence: 99%